Gender and age structure as risk factors of carotid artery stenosis and specific themes areas of cartography - Preradović, Ljubiša; Đajić, Vlado; Jakovljević, Gordana (Decision Making: Applications in Management and Engineering, 2018)
The project on the prevention of a stroke was implemented in the period between 2012 –2017in the Republic of Srpska, when 38,863 patients of both genders were examined. Each of the patients underwent ultrasound examination of blood vessels of the neck on both sides. All the examinations are standardized and carried out by specially trained researchers. Presentation of the The project on the prevention of a stroke was implemented in the period between 2012 –2017in the Republic of Srpska, when 38,863 patients of both genders were examined. Each of the patients underwent ultrasound examination of blood vessels of the neck on both sides. All the examinations are standardized and carried out by specially trained researchers. Presentation of the results of research included descriptive statistics and a certain statistical test, which showed that there is a statistically significant difference in carotid artery stenosis in male and female patients. Geographic Information System was used for mapping the carotid artery stenosis with the aim of determining the susceptibility of the population of a particular area, city and/or municipality to this disease and predicting it. Epidemiological patterns that have been created show the connection between age structure and particular area.results of research included descriptive statistics and a certain statistical test, which showed that there is a statistically significant difference in carotid artery stenosis in male and female patients. Geographic Information System was used for mapping the carotid artery stenosis with the aim of determining the susceptibility of the population of a particular area, city and/or municipality to this disease and predicting it. Epidemiological patterns that have been created show the connection between age structure and particular area.